Evaluation of the Surveillance and Epidemiological Aspects of Cutaneous Leishmaniasis in Babylon Province, Iraq - Mohammed J. Al-Obaidi; Hayder B. Ali (Iraqi Journal of Science, 2021)
Leishmaniasis diseases constitute an important public health problem in both tropical and subtropical areas. The aim of this study is to evaluate the epidemiological situation of cutaneous leishmaniasis (CL) in Babylon province, Iraq. The current work included the recording of 142 new cases of CL infection in Babylon province for the period from November 2019 to February 2020. Male infection was represented by 87 cases (61.27%), while females composed 55 samples (38.73%), with a significant difference (p<0.05) between the two groups. The age group of 5-14 years was found to have the highest recorded CL cases (56; 39.44%), while the age group of less than one year had the lowest cases (1; 0.70%), with the differences being significant at p<0.05. Al-Gazali location was found to include the highest recorded CL cases (29; 20.42%), whereas Kish location had the lowest cases (1; 0.70%). The dry type of CL lesions was represented in 112 cases (78.9%), while the wet type was represented 30 cases (21.1%). The ulcero-crusted form of CL sores was more frequent (105; 73.7%), followed by the papulonodular form (30; 21.1%). According to the location of lesions, the upper limb lesions were more frequent (90; 63.16%), followed by the lower limb lesions (37; 26.32%). About 82 (57.9%) of the recorded CL cases were appearing as new cases, whereas 60 cases (42.1%) were recorded as a relapse after treatment. The study concludes that CL is highly distributed in Babylon province.